Sedation Analgesia for Orthopedic Procedures: An Analysis of Cost and Length of Stay in a Level 1 Trauma Center. Issue 4 (December 2020) - Ghasem, Alexander D.; Huntley, Samuel R.; Butler, Alexander J.; Geller, Joseph S.; Summers, Spencer H.; Dodds, Seth D.
Abstract : Orthopedic reductions can be performed using a wide range of sedation types. Ideally, minimal sedation is applied in the emergency department (ED). In our institution, however, conscious sedation is performed in the ED but is largely unavailable in our trauma center (TC). Therefore, we retrospectively evaluated clinical outcomes and monetary costs associated with identical procedures performed in these different locations. A total of 297 patients were identified: 189 were treated in the TC, and 108 were managed in the ED. A subset of patients were matched by age, injury, and Injury Severity Score. Medical charts were reviewed to identify total charges and length of stay (LOS) for patients presenting to the TC versus the ED. Pearson χ 2 test or Fisher exact test were used to compare categorical variables while Student t test or Mann-Whitney U test were used to compare continuous variables between the matched groups. Mean LOS for patients presenting to the TC (50.4 h, SD=55.8 h) was higher ( P =0.015) than for patients presenting to the ED (13.0 h, SD=9.8 h). Mean procedural charges for patients presenting to the TC ($3, 878, SD=$1272) were higher ( P =<0.0001) than for patients presenting to the ED ($1500, SD=$514.5). Complication rates and outcomes at follow-up showed no apparent difference. Orthopedic bedside procedures performed under conscious sedation afford advantages over general anesthesia including reduced LOS and diminished patient charges. Level of Evidence: Level III–therapeutic.